THE INFLUENCE OF THE PRE-ORGANIZED CRACKS IN THE TENSILE ZONE OF THE REINFORCED CONCRETE BEAM UNDER STATICALLY SHORT-TERM LOADING - A. Chhom; A. M. Kurobanov; F. K. Sametov (Вестник СибАДИ, 2018)
The experimental and theoretical research of the single-span reinforced concrete beam with artificial flaw in tension area under the action of static  short-term loads is performed. The stress-strain state of the structure, based on numerical simulation using finite element software system ANSYS,  is investigated. The results of numerical simulation are compared with the experimental results. It is shown that under static short-term loads, the  beams with pre-cracking have the crack formation of significantly different nature in comparison with the beams without pre-cracking. The  comparative analysis of the experimental data of the reinforced concrete  beam under short-term loading with the results of ANSYS Software program  modeling is carried out in the article. The introduction of the artificial defects  to the tension area of beams would lead to the significant change in the  stress- strain state of the structure and to «mild» nature of its deformation.  The result of such beams deflections under the load is less than deflections of beams without artificial flaws. The recommendations on the beams’ designing with artificial flaws are given in the article. The results of  the modeling cracks’ feasibility in the manufacturing process are demonstrated in the research, because there are the possibilities to regulate the stress fields.